Emotional valence and context of social influences on drug abuse-related behavior in animal models of social stress and prosocial interaction - Neisewander, J.L. (2012)
RATIONALE: Social factors are important determinants of drug dependence and relapse. OBJECTIVES: We reviewed preclinical literature examining the role of social experiences from early life through the development of drug dependence and relapse, emphasizing two aspects of these experiences: 1) whether the social interaction is appetitive or aversive and 2) whether the social interaction occurs within or outside of the drug-taking context. METHODS: The models reviewed include neonatal care, isolation, social defeat, chronic subordination, and prosocial interactions. We review results from these models in regard to effects on self-administration and conditioned place preference established with alcohol, psychostimulants, and opiates. RESULTS: We suggest that in general, when the interactions occur outside of the drug-taking context, prosocial interactions are protective against drug abuse-related behaviors whereas social stressors facilitate these behaviors. By contrast, positive or negative social interactions occurring within the drug-taking context may interact with other risk factors to enhance or inhibit these behaviors. CONCLUSIONS: Despite differences in the nature and complexity of human social behavior compared to other species, the evolving animal literature provides useful models for understanding social influences on drug abuse-related behavior that will allow for research on the behavioral and biological mechanisms involved. The models have contributed to understanding social influences on initiation and maintenance of drug use, but more research is needed to understand social influences on drug relapse.